PENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MELALUI MODEL LEARNING CYCLE 5E - Sisuarni Sisuarni (Jurnal Edukasi dan Penelitian Matematika, 2018)
The mathematical communication is one of ability that whised to be own by students in mathematics learning. In fact that found the mathematical communication ability student of eleventh grade in social science SMA Pembangunan Laboratorium UNP is still low. One effort that can do for overcome these problems is using Learning Cycle 5E model based constructivism. The purpose of this study is to know whether the mathematical communication ability of student who learn using Learning Cycle 5E model is better than the mathematical communication ability of student who learn using conventional learning. Based on data analysis from the final test of mathematical communication ability using nonparametric statistic test by U-Mann Whitney test, it can be conclude the mathematical communication ability of student who learn using Learning Cycle 5E model is better than the mathematical communication ability of student who learn using convensional learning.Keywords — Learning Cycle 5E model, Constructivism, mathematical communication.